RELATIVE IMPACTS OF DIFFERENT DIETS ON THE QUALITIES OF ERI SILK COCOON AND ERI SILK YARN OF FOUR DIFFERENT MUTANTS STRAINS OF PHILOSAMIA RICINI Bsd. - Kumar Gahlaut, Akhilesh; Arjun (International Journal of Research -GRANTHAALAYAH, 2016)
The relative impact of different food plants (diets) namely foliages of castor, kesseru , payam and Topioca plants on the four different mutant strain viz; yellow plain, yellow zebra ,G.B Plain ,G.B Zebra in respect of qualities of their eri cocoon and eri silk yarn have been evaluated under the reeling parameters.Result indicate that among the four different food plants like foliages of castor followed by kesseru have been found evidently better than the foliages of payam and Topiocal in respect of average cocoon weight (gm)4.10,3.55,3.98,3.10,Average shell weight (gm) 0.55,0.45,0.52,0.41,Average shell ratio 13.91,12.0,13.0,11.55,Average lengt- h of silk yarn (mtrs) 2510,2350,2498,2285,Average size of erisilk(D)13D,11D,12D,19D,Average production of eri silk per hr(gm)13.70,12.50,13.10,11.95,Average tenacity of fibre (g/d) 14.0,11.0,12.0,10.0.As far as qualitative differences of all the four food plants in relation to qualities of eri cocoon and eri silk yarn are concerned the castor alongwith kesseru food plants have achieved the status of supremacy primary food plant and payam and tapioca the states of secondary food plants .These variation show that the qualities and production of eri silk cocoon and eri silk yarn depends on the different food plants.